2018
DOI: 10.1161/jaha.117.007893
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle Myosin Light Chain Kinase: A Key Player in Intermittent Hypoxia‐Induced Vascular Alterations

Abstract: BackgroundObstructive sleep apnea is characterized by repetitive pharyngeal collapses during sleep, leading to intermittent hypoxia (IH), the main contributor of obstructive sleep apnea–related cardiovascular morbidity. In patients and rodents with obstructive sleep apnea exposed to IH, vascular inflammation and remodeling, endothelial dysfunction, and circulating inflammatory markers are linked with IH severity. The nonmuscle myosin light chain kinase (nmMLCK) isoform contributes to vascular inflammation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…The proportions of the different fibrillar collagen types in the mice were further assessed using polarized light microscopy. Collagen I was mature and stained red-orange, while collagen III was immature and stained green [37]. The collagen maturation (collagen I/III ratio) was reduced by~50% in the ApoE −/− ;Nampt-Tg mice compared with that in the ApoE −/− mice (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The proportions of the different fibrillar collagen types in the mice were further assessed using polarized light microscopy. Collagen I was mature and stained red-orange, while collagen III was immature and stained green [37]. The collagen maturation (collagen I/III ratio) was reduced by~50% in the ApoE −/− ;Nampt-Tg mice compared with that in the ApoE −/− mice (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Images of Masson's trichrome staining were acquired via Leica microscopy and used to quantify the number of necrotic core and the collagen content (blue staining area). Picrosirius red-stained sections were examined under bright-field illumination for the general collagen content or polarized light for fibrillary collagen observations, in which collagen I appears red-orange and collagen III appears green [37].…”
Section: Histology Analysismentioning
confidence: 99%
“… 43 , 44 Intermittent hypoxia in OSAS patients may increase the levels of oxidative stress and inflammatory cytokines, leading to endothelial cell dysfunction, arteriosclerosis, and subsequent stroke. 45 , 46 Previous studies have shown that both short and long sleep duration are predictors of ischemic stroke. 47 , 48 Inadequate sleep could also impair insulin sensitivity, increase sympathetic nervous system and cortisol levels, and alter inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…All these processes are involved in the formation of AS and related cardiovascular diseases. Further, other proteins were found to participate in AS formation in IH, such as, non-muscle myosin light chain kinase which was discovered in the mouse model ( 23 ). Interestingly, recent studies have also shown that IH and oxidative stress can activate the protective mechanism of endothelial cell-colony forming units in a cell model extracted from healthy volunteers, which is closely linked with vascular function and maintains vascular health ( 24 ).…”
Section: Mechanismmentioning
confidence: 99%